Mood instability is a common feature of mental health disorders and is associated with poor clinical outcomes. Issue 5 (21st May 2015) - Patel, Rashmi; Lloyd, Theodore; Jackson, Richard; Ball, Michael; Shetty, Hitesh; Broadbent, Matthew; Geddes, John R; Stewart, Robert; McGuire, Philip; Taylor, Matthew
Abstract : Objectives: Mood instability is a clinically important phenomenon but has received relatively little research attention. The objective of this study was to assess the impact of mood instability on clinical outcomes in a large sample of people receiving secondary mental healthcare. Design: Observational study using an anonymised electronic health record case register. Setting: South London and Maudsley NHS Trust (SLaM), a large provider of inpatient and community mental healthcare in the UK. Participants: 27 704 adults presenting to SLaM between April 2006 and March 2013 with a psychotic, affective or personality disorder. Exposure: The presence of mood instability within 1 month of presentation, identified using natural language processing (NLP). Main outcome measures: The number of days spent in hospital, frequency of hospital admission, compulsory hospital admission and prescription of antipsychotics or non-antipsychotic mood stabilisers over a 5-year follow-up period. Results: Mood instability was documented in 12.1% of people presenting to mental healthcare services. It was most frequently documented in people with bipolar disorder (22.6%), but was common in people with personality disorder (17.8%) and schizophrenia (15.5%). It was associated with a greater number of days spent in hospital (β coefficient 18.5, 95% CI 12.1 to 24.8), greater frequency of hospitalisation (incidence rate ratio 1.95, 1.75 to 2.17), greater likelihood of compulsory admission (OR 2.73, 2.34 to 3.19) and an increased likelihood of prescription of antipsychotics (2.03, 1.75 to 2.35) or non-antipsychotic mood stabilisers (2.07, 1.77 to 2.41). Conclusions: Mood instability occurs in a wide range of mental disorders and is not limited to affective disorders. It is generally associated with relatively poor clinical outcomes. These findings suggest that clinicians should screen for mood instability across all common mental health disorders. The data also suggest that targeted interventions for mood instability may be useful in patients who do not have a formal affective disorder.